1998
DOI: 10.1094/cchem.1998.75.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Springiness of Pancake and Its Relation to Binding of Prime Starch to Tailings in Stored Wheat Flour

Abstract: Cereal Chem. 75(1):37-42Wheat flours were stored at room temperature (15-25°C), 40, 60, 80, and 100°C for various times. The baking performance of these flours was then evaluated in terms of the springiness of pancakes (recovery from crushing). Baking performance improved with increased storage time at each temperature. Brabender Amylograph tests of the flours indicated that the onset temperature in viscosity decreased with increased storage time at each temperature. When the flours were fractionated by acetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…Dry-heated prime starch and tailings fraction were adsorbed to oil and sedimented with oil. Seguchi (1990Seguchi ( , 1993 and Seguchi et al (1998) reported that stored wheat flour (at room temperature, 40, 60, 80, and 100°C for different times) also improved pancake springiness, and suggested that this improvement may be caused by the hydrophobicity of the prime starch fraction (Seguchi 1984(Seguchi , 1993. Next, we examined whether any increase of springiness of pancakes baked with reconstituted wheat flour composed of both dry-heated prime starch and tailings fractions and unheated water solubles and gluten fractions was obtained when the dry-heating duration for prime starch and tailings fractions was changed from 0 to 30, 60, 90, and 120 min at 120°C.…”
Section: Resultsmentioning
confidence: 99%
“…Dry-heated prime starch and tailings fraction were adsorbed to oil and sedimented with oil. Seguchi (1990Seguchi ( , 1993 and Seguchi et al (1998) reported that stored wheat flour (at room temperature, 40, 60, 80, and 100°C for different times) also improved pancake springiness, and suggested that this improvement may be caused by the hydrophobicity of the prime starch fraction (Seguchi 1984(Seguchi , 1993. Next, we examined whether any increase of springiness of pancakes baked with reconstituted wheat flour composed of both dry-heated prime starch and tailings fractions and unheated water solubles and gluten fractions was obtained when the dry-heating duration for prime starch and tailings fractions was changed from 0 to 30, 60, 90, and 120 min at 120°C.…”
Section: Resultsmentioning
confidence: 99%
“…As indicated in Fig. With gradual decreases in temperature from 120°C, it was necessary to prolong the heat treatment time to obtain the same hydrophobicity of the starch granules [21]. Both are necessary to obtain a spongelike texture.…”
Section: The Role Of Heated Starch Granules In the Pancake Baking Promentioning
confidence: 99%
“…Fractionation of Wheat Flour with Acetic Acid (pH 3.5) Wheat flour was fractionated by the method of Seguchi et al, (1998). The homogenization step was performed by means of a mortar and pestle (Nittokagaku Co., Ltd., ANM-150 Type, Nagoya, Japan; the mortar and pestle were rotated at 120 and 70 rpm, respectively) (Seguchi et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…The homogenization step was performed by means of a mortar and pestle (Nittokagaku Co., Ltd., ANM-150 Type, Nagoya, Japan; the mortar and pestle were rotated at 120 and 70 rpm, respectively) (Seguchi et al, 1998). Flour (50 g) was mixed with 150 mL of water and the mixture was homogenized for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%